PRIORITIES OF THE STATE POLICY OF DEOFFSHORIZATION OF TAXES - LUPAK, R.; NAKONECHNA, N.; KUNYTSKA-ILIASH, M. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The preconditions for distinguishing the main characteristics of the need to develop and implement a state policy of deoffshorization of taxes are identified. The importance of creating a regulated business environment in the country is indicated, in which the state ensures competitiveness, transparency, motivation of activity, and enterprises responsibly adhere to fiscal obligations. The advantages and disadvantages of offshorization of the economy are highlighted, which allowed to draw conclusions about the priority of the country’s policy of tax deoffshorization. It is concluded that it is important to develop an effective system of monitoring and control over the use of offshore mechanisms by enterprises that create risks to economic development and worsen its security. The directions of realization of the state policy of deoffshorization of taxes are defined: normative-legal; financial and investment; technical and technological; social and humanitarian; economic resources; market and infrastructure; information-analytical; institutional and organizational. According to each direction the instruments of the state policy of deoffshorization of taxes are defined. Appropriate state policy should be implemented in the direction of reducing the attractiveness of offshore mechanisms and strengthening the tax liability of enterprises, while creating all possible conditions for this. The function of the state is, on the one hand, to provide sufficient motivation to increase the activity of offshore companies, and, on the other hand, to prevent budget losses of money capital, which can accumulate in the unfair use of offshore benefits. It is concluded that the state policy of tax offshoring should become one of the priorities in the country's efforts to adapt to globalization.
Keywords: deoffshorization; taxes; public policy; offshore territories; tax payments